Effects of α5 GABAA receptor modulation on social interaction, memory, and neuroinflammation in a mouse model of Alzheimer's disease. (13th July 2022) - Aranđelović, Jovana; Santrač, Anja; Batinić, Bojan; Todorović, Lidija; Stevanović, Vladimir; Tiruveedhula, Veera Venkata Naga Phani Babu; Sharmin, Dishary; Rashid, Farjana; Stanojević, Boban; Cook, James M.; Savić, Miroslav M.
Abstract: Aims: GABAergic modulation involved in cognitive processing appears to be substantially changed in Alzheimer's disease (AD). In a widely used 5xFAD model of AD, we aimed to assess if negative and positive allosteric modulators of α5 GABAA receptors (NAM and PAM, respectively) would affect social interaction, social, object and spatial memory, and neuroinflammation. Methods: After 10‐day treatment with PAM, NAM, or solvent, 6‐month‐old transgenic and non‐transgenic 5xFAD mice underwent testing in a behavioral battery. Gene expressions of IL‐1β, IL‐6, TNF‐α, GFAP, and IBA‐1 were determined in hippocampus and prefrontal cortex by qPCR. Results: PAM treatment impaired spatial learning in transgenic females compared to solvent‐treated transgenic females, and social recognition in transgenic and non‐transgenic males. NAM treatment declined social interaction in transgenic and non‐transgenic males, while had beneficial effect on cognitive flexibility in non‐transgenic males compared to solvent‐treated non‐transgenic males. Transgenic animals have not fully displayed cognitive symptoms, but neuroinflammation was confirmed. NAM reduced proinflammatory gene expressions in transgenic females and astrogliosis in transgenic males compared to pathological controls. Conclusion: PAM and NAM failed to exert favorable behavioral effects in transgenic animals. Suppression of neuroinflammation obtained with NAM calls for more studies with GABAergic ligands in amyloid beta‐ and/or tau‐dependent models with prominent neuroinflammation. Abstract : MP‐III‐022 and PWZ‐029, as negative and positive allosteric modulators of α5 GABAA receptors, respectively, exert negligible effects on social interaction, social, object, and spatial memory in 5xFAD mouse model of Alzheimer's disease. PWZ‐029 reduces proinflammatory gene expressions in transgenic females and astrogliosis in transgenic males, which justifies further studies with GABAergic ligands in models of Alzheimer's disease.